Women Self-Help Groups and Women Empowerment - A Case Study of Mahila Arthik Vikas Mahamandal - Lokhande, Murlidhar A. (Indian Journal of Marketing, 2010)
Women empowerment has become a catchword today and has got a significant place in socio-economic development programmes of the government. And why not? Women constitute half of the world population and contribute substantially to the all round development of the world. However, majority of them are the poor, oppressed, underprivileged and discriminated. The World Bank in its report (2006) aptly observes that women are often denied property and inheritance rights. An inequality trap may prevent generations of women from getting educated; restrict their participation in labour market. Prof. Amartya Sen (1995) pointed out that gender tolerance of gender inequality is closely related to notions of legitimacy and correctness. In family behavior, inequalities between men and women are accepted as natural or appropriate. Sometimes, the decisions relating to inequalities are taken and executed by the women themselves. In the new world order, no country can march ahead without the inclusion of women in the development process. Naturally, it becomes imperative to enable women, particularly poor rural women, for accepting the challenges and actively participate in the development process.